Influence of LEAP2 (Liver Expressed Antimicrobial Peptide-2) and Ghrelin Binding to GHSR Gene Receptor as Factors Obesity Incidence: A Literature Review - Asman Hitopik; Ahsanal Kasasiah; Jekmal Malau (Universitas Labuhanbatu, 2024)
Obesity is a serious issue in global health, which requires a more comprehensive understanding for the development of effective therapies. This study explores the role of Liver-Expressed Antimicrobial Peptide 2 (LEAP2) and its interaction with Ghrelin in regulating Growth Hormone Secretagogue Receptor (GHSR) as a potential obesity event. This method used in this review is a systematic literature analysis. The results obtained show that LEAP2, originally known as an antimicrobial, plays a significant role in metabolic regulation and body weight regulation. LEAP2 acts as a Ghrelin antagonist, reduces orexigenic effects and inhibits food intake, and exerts positive effects in tackling the effects of obesity such as hyperlipidemia and inflammation. The study also highlighted the potential of LEAP2 as a therapeutic target in obesity treatment, with palmitoylation modification showing increased stability and effectiveness of LEAP2. However, further understanding and clinical trial studies are needed to validate the preclinical findings and evaluate the long-term effects of LEAP2 regulation on human body weight and metabolic health, thus providing a basis for exploring potential clinical applications in future anti-obesity drug development